Religious Culture in Peacebuilding Education - Prasojo, Zaenuddin Hudi (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
Religion has been examined in various academic disciplines, both mono and interdisciplinary with various accompanying issues, including issues regarding the relationship between religion and culture. This article seeks to show that in the context of peacebuilding education, religious culture plays an important role. This study employs a library research approach. In Indonesia, peacebuilding theories suggest the need for Islamic education as the majority religion in order to the support transformation process relating to changes in negative peace, positive peace, structural violence, root causes of conflict and sustainable peace. This article reveals the process and steps to improve peacebuilding in the implementation of Islamic education. This study is very important to shape a peacebuilding culture in Islamic education where the core values of peacebuilding in Islamic education include the meanings of salām (peace), humanity, harmony and peace, Dar-al-Salam (Home of Peace), peaceful justice through jihad, nonviolence in Islam, justice in Islam and human rights. These core values of peacebuilding education in Islam need to be disseminated and cultivated in all Islamic educational institutions.